Mosque Management for the Prosperity of the Congregation in Mosque Typology in Kendal Regency, Community Empowerment Perspective - Saerozi; Nihayah, Ulin; Umami, Riza; Syafik Mursid, Ahmad; Fahmi Azizy, Dimas (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
The prosperity of the mosque refers to managing the aspects of Idarah, Imarah, and Riayah in accordance with the standards set by the Ministry of Religious Affairs, as well as realizing the Indonesian Mosque Council’s/Dewan Masjid Indonesia (DMI) mission to promote the prosperity of mosques. This study aims to assess the achievement of mosque management standards based on the typology of mosques in Kendal Regency and to identify the efforts carried out to meet these standards. The research emphasizes a community-empowerment perspective, considering the crucial role of public participation in supporting mosque prosperity. Using a descriptive qualitative method supported by simple quantitative data, the study describes field conditions obtained through interviews, observations, and documentation. The data were analyzed inductively using a qualitative descriptive approach. The findings show that various mosque types in Kendal Regency—such as Masjid Jami' Baitussalam, Masjid Besar Al Muttaqin, and Masjid Agung Kendal—function not only as worship spaces but also as centers of community empowerment. These mosques have initiated programs in education, including tafsir classes, religious learning, and skills training. They also provide social services, including aid distribution and free medical treatment, and support economic empowerment through bazaars, small enterprises, and entrepreneurship training to enhance community welfare.